Features of the coronavirus disease course in young children - Kosmynina, N. S.; Avramenko, I. Yu. (Zaporozhye Medical Journal, 2021)
The aim. To analyze the features of the coronavirus disease course in young children. Materials and methods. We analyzed case histories of 60 children aged 0 to 3 years who were hospitalized to the Lviv Regional Children’s Clinical Hospital “OHMATDYT” in the period from April to December 2020 with a diagnosis of coronavirus disease. Out of the 60 children 36 (60 %) were boys and 24 (40 %) were girls. Laboratory studies on the presence of SARS-CoV-2 virus RNA were performed in samples of nasal and pharyngeal swabs by PCR at the State Institution “Lviv Regional Laboratory Center of the Ministry of Health of Ukraine”. Blood and urinary laboratory tests were performed on the basis of the Laboratories in Lviv Regional Children’s Clinical Hospital “OHMATDYT”. The result were statistically processed using Excel software from Microsoft Office 2019 packages. Quantitative characteristics were given as M ± m (arithmetic mean ± standard deviation of the arithmetic mean). Results. It was found that 40% of children under 1 year old and only 15% from 1 to 3 years old were hospitalized on the first day of the disease. Parents of sick children in 51 (85 %) cases confirmed the presence of contact with infected family members. The analysis of the disease clinical manifestations showed that during the disease course, most children with coronavirus disease had the following clinical manifestations: fever, runny nose, cough, abdominal pain, diarrhea, and general weakness. Lymphopenia, which is the most common laboratory finding in adults with COVID-19, was found only in 28 % of children hospitalized to the Regional Children’s Clinical Hospital “OHMATDYT”. The presence of complications in the form of pneumonia was observed in 5 children, which amounted to 8.3 %. The average duration of inpatient treatment for children under 1 year of age was 7 days, and it was 6 days for children between 1 and 3 years of age. Conclusions. It was found that 85% of child inpatients were in contact with family members in whom the presence of SARS-CoV-2 infection was confirmed. The main manifestations of coronavirus disease were fever ˃38 °C and general weakness in more than 55% of children aged 0 to 3 years. The level of leukocytes within the age norm was observed in 46.6% of children, leukopenia– in 35.0%, and lymphopenia– in 28.3%. The course of the disease among young children was mild, and only 8.3% of children had the moderately severe course, complicated by pneumonia.